2011
DOI: 10.1007/s00253-011-3781-6
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and genetic analysis of a cutinase-type polyesterase from a thermophilic Thermobifida alba AHK119

Abstract: Recombinant polyesterase (Est119) from Thermobifida alba AHK119 was purified by two chromatography steps. The final protein was observed as a single band in SDS-PAGE, and the specific activity of Est119 for p-nitrophenyl butyrate was 2.30 u/mg. Purified Est119 was active with aliphatic and aliphatic-co-aromatic polyesters. Kinetic data indicated that p-nitrophenyl butyrate (pNPB) or hexanoate was the best substrate for Est119 among p-nitrophenyl acyl esters. Calcium was required for full activity and thermosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 37 publications
3
81
0
Order By: Relevance
“…It can therefore be assumed that the inhibition was caused by the ester bonds of MHET and BHET occupying the substrate binding site of TfCut2. In a previous study, EG has been shown to inhibit the hydrolysis of the model ester p-nitrophenyl butyrate by the polyester hydrolase Est119 from Thermobifida alba, an enzyme homologous to TfCut2 [44]. However, the binding site of EG in Est119 was assumed not to be directly involved in the ester bond hydrolysis [45].…”
Section: Discussionmentioning
confidence: 96%
“…It can therefore be assumed that the inhibition was caused by the ester bonds of MHET and BHET occupying the substrate binding site of TfCut2. In a previous study, EG has been shown to inhibit the hydrolysis of the model ester p-nitrophenyl butyrate by the polyester hydrolase Est119 from Thermobifida alba, an enzyme homologous to TfCut2 [44]. However, the binding site of EG in Est119 was assumed not to be directly involved in the ester bond hydrolysis [45].…”
Section: Discussionmentioning
confidence: 96%
“…The genes of several synthetic polyester hydrolases within the abH05 family have shown to code for an N-terminal Gram-positive signal peptide containing 29-58 amino acid residues (Chertkov et al, 2011;Dresler, van den Heuvel, Muller, & Deckwer, 2006;Hegde & Veeranki, 2013;Hu et al, 2010;Kleeberg et al, 1998Kleeberg et al, , 2005Lykidis et al, 2007;Sulaiman et al, 2012;Thumarat et al, 2012), further confirming the identity of these enzymes as secreted proteins with mature protein sequences containing 258-262 amino acid residues. Most of the enzymes from the Thermobifida genus are produced as homologous isoenzymes with a high sequence identity of 92-95% for the mature proteins without the signal peptides (Chen et al, 2008;Hegde & Veeranki, 2013;Herrero Acero et al, 2011;Hu et al, 2010;Thumarat et al, 2012). The other polyester hydrolases in this family also show a sequence similarity of more than 60% (Table 7.1).…”
Section: Classification Of Actinomycete Polyester Hydrolasesmentioning
confidence: 90%
“…Actinomycetes that produce polyester hydrolases Synthetic polyester hydrolases have been detected in various moderate thermophilic actinomycetes, including Thermobifida fusca (Alisch et al, 2004;Alisch-Mark, Herrmann, & Zimmermann, 2006;Billig, Oeser, Birkemeyer, & Zimmermann, 2010;Chen et al, 2008;Feuerhack et al, 2008;Gouda, Kleeberg, van den Heuvel, Muller, & Deckwer, 2002;Hegde & Veeranki, 2013;Herrero Acero et al, 2011;Kleeberg, Hetz, Kroppenstedt, Muller, & Deckwer, 1998;Kleeberg, Welzel, Vandenheuvel, Mü ller, & Deckwer, 2005;Oeser et al, 2010), T. alba (Hu, Thumarat, Zhang, Tang, & Kawai, 2010;Thumarat, Nakamura, Kawabata, Suzuki, & Kawai, 2012), T. cellulosilytica , T. halotolerans , and Thermomonospora curvata . Actinomycetes that produce polyester hydrolases Synthetic polyester hydrolases have been detected in various moderate thermophilic actinomycetes, including Thermobifida fusca (Alisch et al, 2004;Alisch-Mark, Herrmann, & Zimmermann, 2006;Billig, Oeser, Birkemeyer, & Zimmermann, 2010;Chen et al, 2008;Feuerhack et al, 2008;Gouda, Kleeberg, van den Heuvel, Muller, & Deckwer, 2002;Hegde & Veeranki, 2013;Herrero Acero et al, 2011;Kleeberg, Hetz, Kroppenstedt, Muller, & Deckwer, 1998;Kleeberg, Welzel, Vandenheuvel, Mü ller, & Deckwer, 2005;Oeser et al, 2010), T. alba (Hu, Thumarat, Zhang, Tang, & Kawai, 2010;Thumarat, Nakamura, Kawabata, Suzuki, & Kawai, 2012), T. cellulosilytica , T. halotolerans , and Thermomonospora curvata .…”
Section: Identification Of Synthetic Polyestermentioning
confidence: 99%
See 2 more Smart Citations